Do Social Relations Affect Economic Welfare? A Microeconomic Empirical Analysis - Giacomo Degli Antoni (Fondazione Eni Enrico Mattei (FEEM), 2007)
Over the last few years, many studies have shown that social networks affect the socioeconomic development. This paper presents evidence, through the Italian microdata representative of the entire Italian population, that the quality and quantity of interpersonal relations of agents can increase their economic welfare. Two proxies of interpersonal relations at an individual level are considered: a proxy for the density and one for the quality of network structure of personal contacts. Both seem to have a positive effect on the level of household economic welfare of agents. This result proves robust to the inclusion of a variety of control variables and to the use of different econometric methods.
Keywords: D10; Z13; 330; Networks; Social Interactions; Household Economic Welfare; Microdata; Fuzzy Logic; Soziale Beziehungen; Wohlfahrtsanalyse; Soziales Netzwerk; Lebensqualität; Privater Haushalt; Italien